Hubungan Motivasi Belajar Dengan Kemandirian Belajar Siswa Kelas IX MTSN 28 Jakarta Pada Masa Pandemi - Salohot Batubara; Renti Rahmawati Nugroho (Guidance : Jurnal Bimbingan dan Konseling, 2021)
The purpose of this thesis is to determine the relationship between learning motivation and independent learning of class IX students of MTSN 28 Jakarta during the pandemic. The method used in the hypothetical test research uses the product moment correlation test (rxy). The population in this study were all students of class IX at Madrasah Tsanawiyah Negeri 28 East Jakarta, totaling 157 students. and the research sample amounted to 157 students. As for the sampling technique used was saturated samples. The learning motivation instrument before being tested was 64 statements after being tested for the validity of 38 statements. While the instrument of learning independence before being tested was 64 statements after being tested for the validity of 53 statements. Hypothesis test results show that the Product Moment Correlation analysis of the two variables is r = 0.659. Sig. 0.000 <0.05 H0 is rejected and accepts H1. means that there is a relationship between learning motivation and learning independence. This variable is significant because the significance number is <0.001.